Engineering the glyoxylate cycle for chemical bioproduction - Yang, Peng; Liu, Wenjing; Chen, Yanan; Gong, An-Dong (Frontiers in Bioengineering and Biotechnology, 2022)
With growing concerns about environmental issues and sustainable economy, bioproduction of chemicals utilizing microbial cell factories provides an eco-friendly alternative to current petro-based processes. Creating high-performance strains (with high titer, yield and productivity) through metabolic engineering strategies is critical for cost-competitive production. Commonly, it is inevitable to fine-tuning or rewire the endogenous or heterologous pathways in such processes. As an important pathway involved in the synthesis of many kinds of chemicals, the potential of glyoxylate cycle in metabolic engineering has been studied extensively these years. Here, we review the metabolic regulation of glyoxylate cycle and summarize recent achievements in microbial production of chemicals through tuning of the glyoxylate cycle, with a focus on studies implemented in model microorganisms. Also, future prospects for bioproduction of glyoxylate cycle-related chemicals are discussed.